We are Big Data The Future of the Information Society - Klous, Sander; Wielaard, Nart (Atlantis Press : Imprint: Atlantis Press, 2016)
Sander Klous holds a PhD in High Energy Physics and contributed to the discovery of the Higgs boson at CERN (Nobel prize 2013). Klous works at KPMG and is professor in Big Data at the University of Amsterdam. Nart Wielaard is a self-employed consultant and business writer. He develops compelling and clear stories on complex topics for a broad range of clients. Wielaard specializes in the domain where technology, society and business meet. .